Elastoplastic stability of thin rectangular plates under complex and impure loading - Ham, Vu Cong (Vietnam Journal of Mechanics, 2001)
This paper deals with investigation of the elastoplastic stability of thin rectangular plates. The plate considered herein is subjected to the biaxial compressive forces which are assumed to be linearly distributed along every its edge. The governing equations of the problem are formulated with applying the elastoplastic process theory whereas Bubnov - Galerkin method is used to calculate the critical forces. In the paper the author proposes a new method to determine the elements of the matrix concerned with the instability moment of the structure and applies the Gaussian quadric method for integral calculation. Some results of numerical calculations are also presented in the paper.